IMPLEMENTASI MATA PELAJARAN KITABAH DALAM MENINGKATKAN KEMAMPUAN BACA TULIS ARAB GUNDUL SANTRI MADRASAH DINIYAH - Moh. Nur Shodiq; Hasan Basri (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
Students who are slow to learn and have low achievement can also be caused by IQ factors or can be family factors. According to research by Binet and Simon, mentally weak children have an IQ between 50 and 69, classified as slow learners. This study aims to describe the implementation of the kitabah subject in improving the ability to read and write bald Arabic at Madrasah Diniyah Al Irsyadiyah. The type of research conducted is qualitative research with data collection techniques namely observation, interviews, and documentation. The results of this study are that the implementation of the Kitabah subject by Islamic religious education teachers is the right method in the process of increasing bald Arabic reading and writing. The obstacle faced by these teachers in reading and writing Arabic is that there is a lack of educators in the field of Islam, children do not receive guidance at home while reading and writing Arabic in Madrasah Diniyah is very limited. The solution carried out by Islamic religious education teachers overcomes the obstacles faced by students in this case by means that the teacher must work together with the parents or guardians of students or students.